ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (Studi Kasus PT. Bank Tabungan Negara Tbk Periode 2018-2022) - Cristine Natalia (Jurnal Cakrawala Ilmiah, 2024)
Bank BTN experienced a fairly high increase in non-performing loans during the Covid-19 pandemic in 2019 because many customers were unable to repay their credit, this triggered researchers to want to know what the health level of Bank BTN was before the pandemic and after the Covid-19 pandemic. The aim of this research is to determine the health level of PT. Bank Tabungan Negara Tbk for the 2018-2022 period using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). This type of research uses quantitative with a descriptive approach. The population in the research is Bank BTN's financial reports and the sample for this research is the period of analyzing Bank BTN's financial reports, namely for five years (2018-2022) and the sample was obtained using a purposive sampling technique. The research results show that the overall financial performance of PT. Bank Tabungan Negara Tbk during the 2018-2022 period using the RGEC method, namely obtaining an average of 76.67% to 80.00%, the composite rating obtained by Bank BTN is at (PK-2) which can be seen from the four aspects measured in the Risk Profile, GCG, Earnings, and Capital as a whole are in a Healthy rating